Philosophical Analysis of Embedded Economy on The Jamaah Islamiyah Terrorist Group in Indonesia - Joko Dwi Harsono; Fristian Hadinata (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This research seeks to provide an explanation of how economics, in the context of efforts or methods to meet needs, is embedded in the behavior of terrorist groups in Indonesia based on a commitment to violence that hides behind the dogma of religious ideology. As Karl Polanyi proposed, economic embeddedness defines the economy as a product of social relations based on wisdom values and mutually sufficient mutual relations between individuals and groups under the auspices of local wisdom. It turns out that other attributes are attached to embedded economics apart from ethical values, namely the commitment of social groups to the path of violence. This research used a qualitative approach that is a critical analysis of actual problems occurring in society, namely the existence of an economic mode in the movement of the terrorist group Jemaah Islamiyah (JI) in Indonesia. The research results found that economic motives play a role in the actions carried out by terrorist groups; in the context of JI, social currency is used in monetary exchange. The Indonesian government has implemented the principle of redistribution with a multidimensional approach in dealing with terrorism, one of which is Karl Polanyi's Economic Embeddedness approach, which involves the redistribution of resources and integration of terrorist groups into broader society, as well as the termination of terrorism funding.